Tailoring of magnetic properties of giant magnetoresistance spin valves via insertion of ultrathin non-magnetic spacers between pinned and pinning layers - Kim, Si Nyeon; Choi, Jun Woo; Lim, Sang Ho (NATURE PUBLISHING GROUP, 2019)
The low-field sensitivity of a giant magnetoresistance (GMR) spin valve can be enhanced by tailoring the bias field of the free layer because this sensitivity and bias field are known to show a strong correlation. In this study, the free-layer bias field is reduced considerably to almost zero via the insertion of an ultrathin nonmagnetic spacer between the pinned layer and the pinning layer. The spacer promotes an increase in the density of Neel walls in the pinned layer. This increase, in turn, induces domain-wall-induced magnetostatic interactions of the free poles formed on the Neel walls inside the free and pinned layers. The magnetostatic interactions result in the formation of flux closures that act as pinning sites during the magnetization reversal process and stabilize the antiparallel magnetization state between the free layer and the pinned layer by suppressing the switching of the free layer from the antiparallel state to the parallel state. Furthermore, the spacer offers an additional advantage of increasing the GMR ratio by inducing a specular scattering effect at its top and bottom interfaces. A highly improved low-field sensitivity of 12.01 mV/mA.Oe is achieved in the sample with a Cu/Pt dual spacer.
Keywords: SPECULAR ELECTRON-SCATTERING; EXCHANGE BIAS; THICKNESS